Isolation and characterization of aerial bacteria from a microbiology laboratory environment (Journal of Bio-Science, 2019)
Sterile nutrient agar (NA) plates were exposed to the inner and outer environment of the laboratory for 15 minutes before the commencement of laboratory work in the morning and after closure of activities in the evening after which the plates were incubated at 37oC for 24 hours. Antibiotic susceptibility of the bacterial isolates was done using agar well diffusion technique. The aerial bacterial load outside the laboratory was found to be higher than inside the laboratory. Bacteria isolated include members of the genus Staphylococcus, Bacillus, Lactobacillus, Salmonella, Micrococcus, Streptococcus, Proteus and Escherichia. Bacillus subtilis had the highest frequency of occurrence (31.0%) followed by alpha haemolytic streptococcus (19.0%) while the least frequency of occurrence was shown by Proteus bulgaricus and Proteus species (1.7%). All the bacteria were sensitive to antibiotics tested except Micrococcus luteus. They were equally found to be sensitive to the anti-microbial agent (antiseptic and disinfectant) tested except for the hand sanitizer to which most isolates displayed high resistance. The presence of a wide variety of pathogenic microorganisms in the laboratory shows that the environment requires regular cleaning and disinfection to enhance the safety of staff and students using the laboratory.J. bio-sci. 26: 41-48, 2018